143 BEVERAGE INTAKE AMONG PRESCHOOL CHILDREN AND ITS EFFECT ON WEIGHT STATUS. (1st January 2006) - O'Connor, T.; Yang, S. J.; Nicklas, T.
Abstract : Background: A number of eating patterns have been associated with overweight among preschool-aged children. Recently, 100% fruit juice and sweetened fruit drinks have received a lot of attention as potential sources of high-energy, low-nutrient-dense beverages that could be related to the prevalence of obesity among young children. Objective: To investigate associations between types and amounts of beverages consumed and weight status in preschool-aged children. Methods: Children, 2 to 5 years old, were identified by a secondary analysis of the National Health and Nutritional Evaluation Survey (NHANES) 1999-2002 data. Beverages were classified based on the USDA Food and Nutrient Database for Dietary Studies. Descriptive and chi-square analyses, as well as analysis of covariance, adjusting for age, gender, ethnicity, household income, calories, and physical activity were conducted. Results: Of the 1, 160 children analyzed, 24.1% of the children were overweight or at risk for overweight (body mass index (BMI) $ 85%) and 10.7% were overweight (BMI $ 95%). The prevalence of children who drank milk, 100% fruit juice and fruit drinks, was 83%, 48%, and 44% respectively. Whole milk was consumed by 46.5% and skim milk and 1% milk were consumed by 3.1% and 5.5% of the children, respectively. Preschool children consumed a mean total beverage volume of 26.93 oz/day (SE 0.57); which included 12.32 oz of milk (SE 0.63), 4.70 oz of 100% fruit juice (SE 0.32), and 4.98 oz of fruit drinks (SE 0.38). Weight status of the child had no association with the amount of total beverages, milk, 100% fruit juice, or fruit drink consumed. Daily total energy intake increased with increased consumption of milk (p < .01), 100% fruit juice (p < .001), and fruit drinks (p < .01); however, there was not a statistically significant increase in BMI. Conclusions: Preschool children drink less milk than the 2005 Dietary Guidelines for Americans recommendation of 16 ounces/day and only 8.6% drink low-fat or skim milk, as recommended. On average, preschool children drink less than 6 oz/day of 100% fruit juice. Increased beverage consumption increased the total energy intake of the children, but not their BMI. Prospectively studying preschool children beyond 2 to 5 years old, through their adiposity rebound (5.5-6 years) to see if there is a trajectory increase in their BMI, may help clarify the role of beverage consumption to total energy intake and weight status.